Patent Signals of IPO Performance: Evidence from High- and Low-Tech Industries in Japan (School of Business and Management Institut Teknologi Bandung, 2022)
Abstract: Prior studies pointed to evidence that startups and venture capital (VC) companies tended to use different measures to provide signals to outsiders. This study adds to those previous insights by focusing on established firms’ patenting behaviors and their effect on the amount of money raised at the initial public offering (IPO). Since technology intensity may differ considerably between high and low-tech companies, our main interest in this paper lies on whether the significance of pre-IPO patenting activities as a predictor of IPO performance also varies between these two industry categories. Using cross-sectional data representing 308 Japanese industrial firms’ IPO commitments between 2000 and 2015, we find a robust positive correlation between patent applications and IPO performance. Contrary to the conventional wisdom proposing that high-tech firms with more patenting activities achieve better IPO performance, we show that the signaling power of patenting is stronger for the low-tech companies in our sample: While the high-tech firms do not seem to have significantly benefited from a patent signal, the low-tech firms seem to have attracted external investors more easily due to patenting at the IPO. Keywords: Patent, signal, initial public offering (IPO), high-tech industries, low-tech industries